Whistleblowing System Dan Surprise Audit: Strategi Pencegahan Fraud - Dwi Urip Wardoyo; Muhammad Arya; Desiana Woro Pawestri; Bethari Shakuntala (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
This study aims to examine the strategy of a company in preventing fraud, using a whistleblowing system and a surprise audit. When the Covid-19 pandemic entered Indonesia, many companies experienced a decline in sales so that company revenues decreased. If the company was indicated by fraud, the company's survival would be threatened. Therefore, it is very important for a company to have a fraud prevention strategy which can go through a whistleblowing system and a surprise audit. This study uses a qualitative method. This type of research is included in a literature review study related to fraud prevention strategies, whistleblowing systems and surprise audits